KONTROLER GAIN SCHEDULING UNTUK RUDAL UDARA KE UDARA - Andiarti, Rika (Indonesian Journal of Aerospace, 2005)
A control system for an air-to-air guided missile is developed. Gain scheduling control technique is used to perform the missile flight toward a moving target. The simulation results show that the gain scheduling control technique is effective to obtain the desired missile performance.